2023
DOI: 10.1111/jfr3.12898
|View full text |Cite
|
Sign up to set email alerts
|

Simulation of flash flood peaks in a small and steep catchment using rain‐on‐grid technique

Abstract: The frequency of extreme events is increasing as the consequences of climate change. In steep terrains, flash floods with high‐flow velocities induce erosion and sedimentation with potentially disastrous changes of flood path. Hence, the analysis of flash floods in steep terrains in terms of inundation area and flow‐velocity to identify critical points becomes more important. The output of a flood simulation with a traditional hydrologic model provides the flood hydrograph which must be combined with a hydraul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 55 publications
0
3
0
Order By: Relevance
“…To reproduce the peak in HR2D, more flow volume and a delayed peak were needed. Since the mesh size also controls the runoff volume (Godara et al, 2023b), the cell size for the catchment was decreased to 50 m, which increased the runoff volume. Afterward, Manning's roughness values were increased to delay the peak which resulted in a good calibration of peak flow and timing for event A (Figure 5).…”
Section: Calibration and Single-storm Flood Eventsmentioning
confidence: 99%
See 1 more Smart Citation
“…To reproduce the peak in HR2D, more flow volume and a delayed peak were needed. Since the mesh size also controls the runoff volume (Godara et al, 2023b), the cell size for the catchment was decreased to 50 m, which increased the runoff volume. Afterward, Manning's roughness values were increased to delay the peak which resulted in a good calibration of peak flow and timing for event A (Figure 5).…”
Section: Calibration and Single-storm Flood Eventsmentioning
confidence: 99%
“…In this study, we compare the performance of two hydrodynamic models, TELEMAC-2D (Ligier, 2016) and HEC-RAS 2D (Brunner, 2002) for their Rain-on-Grid (RoG) technique in a steep catchment to find out their limitations and strengths. RoG implementation in TELEMAC-2D (T2D hereafter) has been tested before to model flash floods in a steep and small snow-covered catchment (Godara et al, 2023b), and it was found that the model was able to reproduce single storm flood events but struggled to reproduce all peaks in a sustained flow event with multiple peaks. Therefore, the first objective of this study is to check if HEC-RAS 2D (HR2D hereafter) can achieve equally good results as T2D for simulating single storm flood events.…”
Section: Introductionmentioning
confidence: 99%
“…Users have the flexibility to customize the code to suit their specific needs. The source code of T2D model is customized in this study to use spatially distributed precipitation as input from a previous study [40]. The main inputs required are DTM, roughness values, and boundary conditions such as water flow or water surface elevation.…”
Section: Methods and The Combination Of Snow Routine With Integrated ...mentioning
confidence: 99%
“…Based on findings from a previous study by Godara et al [40] using TELEMAC-2D on the same catchment, parameters such as the antecedent moisture conditions (AMC), roughness, and mesh size were kept constant, and the model was calibrated only for CN values. The calibration results from that study showed that courser the mesh size, drier the catchment, and higher the roughness, the lower the runoff volume and vice versa.…”
Section: Methods and The Combination Of Snow Routine With Integrated ...mentioning
confidence: 99%
“…Development and optimization of tools and approaches towards understanding flooding potential and evaluating flood risk management approaches are also required to improve flood preparedness. This is exemplified in this issue by several studies into new approaches for numerical modelling tools in flood simulation, including the effect of cross‐sectional orientation in a one‐dimensional hydrodynamic model on variability in model flood simulations (Jesna et al, 2023), incorporation of spatially distributed precipitation into a two‐dimensional hydraulic model for a vulnerable, steep‐terrain catchment (Godara et al, 2023), integration of local‐scale features into a hydraulic modelling framework to improve model representation of local urban flood defence infrastructure (Massam et al, 2023), and the relationship between spatiotemporal catchment hydrological processes and the calibration process in hydrological–hydrodynamic models (David et al, 2023). A new modelling approach for critical infrastructure networks that can be disrupted by flooding is explored by Schotten and Bachmann (2023).…”
mentioning
confidence: 99%